2003
DOI: 10.1590/s1676-24442003000100009
|View full text |Cite
|
Sign up to set email alerts
|

Catalase-negative, methicillin-resistant Staphylococcus aureus as a cause of septicemia

Abstract: A catalase-negative methicillin-resistant Staphylococcus aureus (MRSA) was isolated from blood, venous catheter spike and bone marrow collected from an HIV-positive man with lobar pneumonia and sepsis after ten days of hospitalization. The isolate was resistant to oxacillin (positive for penicillin-binding protein 2'), ceftriaxone, clindamycin and clarithromycin, and susceptible to vancomycin. This is the first case of septicemia due to a catalase-negative S. aureus reported in Brazil, and, to our knowledge, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The isolates showed double hemolysis, which gave us the clue and motivated us further to continue with the identification process. The review of the literature revealed reports for catalase-negative S. аureus, but they referred to isolates of human origin [7,[12][13][14] . Piau et al [8] determined a catalasenegative S. аureus strain with point mutations in the katA gene as a possible mechanism for the loss of catalase activity.…”
Section: Discussionmentioning
confidence: 99%
“…The isolates showed double hemolysis, which gave us the clue and motivated us further to continue with the identification process. The review of the literature revealed reports for catalase-negative S. аureus, but they referred to isolates of human origin [7,[12][13][14] . Piau et al [8] determined a catalasenegative S. аureus strain with point mutations in the katA gene as a possible mechanism for the loss of catalase activity.…”
Section: Discussionmentioning
confidence: 99%